Rekontruksi Makna Belajar Transformasi Geometri Berbasis Perspektif Fenomenologi Siswa - Siti Rukayah; Anies Fuady (FKIP Universitas Mataram, 2026)
The learning of geometric transformations in schools is often reduced to procedural understanding, which triggers epistemological barriers and existential anxiety for students. The research problem of this study concerns the essence of students' subjective experiences in the topic of geometric transformations. This study aims to reconstruct the essence of students' subjective experiences in learning this material to fill the gap in the literature that has long been dominated by cognitive-quantitative studies. The novelty of this research lies in revealing the emotional dimension and embodied experience from a first-person perspective. Through a qualitative method with a phenomenological design, data were collected through in-depth interviews and participatory observation of students at one Private Madrasah Aliyah in Kota Batu. The results of the study reveal four main structures of experience: (1) mathematical anxiety operates as a pre-reflective barrier that blocks access to cognition; (2) the phenomenon of embodied cognition where the body and physical gestures become vital anchors in spatial abstraction; (3) the occurrence of silent struggle due to pseudo intersubjectivity in the classroom; and (4) ontological transformation from fear towards self-meaning. The research conclusion emphasizes that learning geometry is not merely a cognitive event, but a phenomenological event that requires a humanistic pedagogical approach by integrating affective, bodily, and social dimensions.